White noise path integral approach in evaluating B-cell density with a Gaussian activation function - Bazar, Jason S.; Aban, Christine Joy G.; Nasir, Alviu Rey B. (2015)
This study presents the calculation of the B cell density using white noise analysis based on the modelling of Perelson and Wiegel. The B cell density represents the population of B cells that stimulated into the prolifereation in shape space. The activation used in this study is a gaussian function. The activation function defines the degree of activation for the B cell population. Evaluating this kind of function gives us a better understanding on how the immune system responds to foreign antigens because according to the work of Perelson, the behavior of antibodies when stimulated by antigens exhibit a log-bell shaped function. When the B cell density equation is plotted, a bell-shape curve is observed in the graph. Also, as we increase the affinity between the antigen and antibody, the response is quicker while the density decreases.
Keywords: Mathematics; Immune system